Feeding practices demonstrated by parents of toddlers: An observational analysis of breakfast, lunch, dinner, and snacks. (1st December 2020) - Moding, Kameron J.; Fries, Lisa R.
Abstract: The aims of the current study were to compare feeding practices and the eating environment (other people present, other people eating, and screen use) observed in families of toddlers across breakfast, lunch, dinner, and snacks. 60 families with toddlers (12–36 months; M  = 24.7 months) video recorded all occasions over the course of a day when the toddler ate or drank. Videos were coded for a variety of feeding practices (e.g., prompts to eat, restriction), other people present and eating, and screen use. Prompts to eat were grouped into autonomy-supportive prompts (ASP) and coercive-controlling prompts (CCP). Results of the study showed different patterns of consistency between meals and snacks depending on the feeding practice examined. CCP were correlated across all eating occasions, including meals and snacks, but ASP, interference, and instruction were only correlated across the primary meals (all p -values < .05). ASP and praise were also more frequently demonstrated during the primary meals compared to snacks ( p -values < .05). Parents also used more interference at dinner compared to both breakfast and snacks. Furthermore, mothers and siblings commonly ate with the toddler, especially during lunch and dinner, but family members infrequently ate with the child during snacks. The percentage of families using a screen was similar for breakfast (38%), lunch (39%), and dinner (33%), but slightly higher for snacks (47%). Together, the results of this study demonstrate notable differences in feeding practices and environmental factors during meals compared to snacks.